Electron jet of asymmetric reconnection. Issue 11 (6th June 2016) - Khotyaintsev, Yu. V.; Graham, D. B.; Norgren, C.; Eriksson, E.; Li, W.; Johlander, A.; Vaivads, A.; André, M.; Pritchett, P. L.; Retinò, A.; Phan, T. D.; Ergun, R. E.; et al.
Abstract: We present Magnetospheric Multiscale observations of an electron‐scale current sheet and electron outflow jet for asymmetric reconnection with guide field at the subsolar magnetopause. The electron jet observed within the reconnection region has an electron Mach number of 0.35 and is associated with electron agyrotropy. The jet is unstable to an electrostatic instability which generates intense waves with E ∥ amplitudes reaching up to 300 mV m −1 and potentials up to 20% of the electron thermal energy. We see evidence of interaction between the waves and the electron beam, leading to quick thermalization of the beam and stabilization of the instability. The wave phase speed is comparable to the ion thermal speed, suggesting that the instability is of Buneman type, and therefore introduces electron‐ion drag and leads to braking of the electron flow. Our observations demonstrate that electrostatic turbulence plays an important role in the electron‐scale physics of asymmetric reconnection. Key Points: Electron outflow jet of asymmetric magnetic reconnection is observed Electron jet is unstable to Buneman‐type instability generating intense electrostatic waves The instability leads to thermalization and braking of the electron jet